2013
DOI: 10.3168/jds.2012-6044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Charm maximum residue limit β-lactam and tetracycline test for the detection of antibiotics in ewe and goat milk

Abstract: The Charm maximum residue limit β-lactam and tetracycline test (Charm MRL BLTET; Charm Sciences Inc., Lawrence, MA) is an immunoreceptor assay utilizing Rapid One-Step Assay lateral flow technology that detects β-lactam or tetracycline drugs in raw commingled cow milk at or below European Union maximum residue levels (EU-MRL). The Charm MRL BLTET test procedure was recently modified (dilution in buffer and longer incubation) by the manufacturers to be used with raw ewe and goat milk. To assess the Charm MRL BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 15 publications
(20 reference statements)
3
23
1
Order By: Relevance
“…In the paper by Nagel et al (2012), Penicillin G residues are found with a suitable limit of detection using two different bioassays, whereas Amoxicillin sensitivity was higher than the MRL for the bioassay based on the growth inhibition of Bacillus subtilis. As regard the use of rapid tests on ewe milk, satisfactory results have been obtained for Amoxicillin and Benzilpenicillin (Beltrán et al, 2013(Beltrán et al, , 2014. In those last papers, contrarily to the results recorded in the present study, suitable results are found also in the detection of Cefazolin.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…In the paper by Nagel et al (2012), Penicillin G residues are found with a suitable limit of detection using two different bioassays, whereas Amoxicillin sensitivity was higher than the MRL for the bioassay based on the growth inhibition of Bacillus subtilis. As regard the use of rapid tests on ewe milk, satisfactory results have been obtained for Amoxicillin and Benzilpenicillin (Beltrán et al, 2013(Beltrán et al, , 2014. In those last papers, contrarily to the results recorded in the present study, suitable results are found also in the detection of Cefazolin.…”
Section: Resultssupporting
confidence: 60%
“…In some papers dealing with sheep milk, different percentages of doubtful (0.6% in the paper by Montero et al, 2005;1% in Althaus et al, 2009) and falsepositive results (0.18% in Comunian et al, 2010) have been reported during the procedures for examination of antibiotics-free samples. False-positive results have been also recorded using a different version of Betastar Combo on individual ewe milk samples: 0.8% by Beltrán et al (2013) and 1.2% for the sole tetracyclines line by Beltrán et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…The Charm MRL BLTET (Charm Sciences Inc., Lawrence, MA, USA) is an example of immunoreceptor Rapid One Step Assay (ROSA®) that detects beta-lactam and tetracycline drugs below EU-MRL in raw milk. Detection capability at or below EU-MRL was optimal for the great majority of beta-lactams and tetracyclines in ewe and goat milk (Beltrán et al, 2013), the specificity (100 minus percentage of non-compliant results obtained for individual milk free of antibiotics) being very high (97.9-100%). Very good performances (detection capability and specificity) were also reported for other receptor-binding assays, such as Betastar Combo test (Neogen Corporation, Lansing, MI, USA), SNAP Betalactam test (IDEXX Laboratories, Westbrook, ME, USA), SNAP Tetracycline test (IDEXX Laboratories), or Twinsensor BT test (Unisensor, Liege, Belgium) (Beltrán et al, 2014a,b).…”
Section: Receptor Binding Assaysmentioning
confidence: 99%
“…calidolactis. Different studies on the sensitivity of microbial tests have been developed in the last two decades by different authors using sheep and goat milk (Contreras et al, 1997;Molina et al, 2003;Sierra et al, 2009a,b;Comunian et al, 2010;Beltrán et al, 2013) and important efforts have been carried out in recent years by manufacturers to improve the performance and sensitivity of microbial tests (IDF, 2010). As a whole, microbial inhibitor tests using Geobacillus stearotermophilus var.…”
Section: Microbial Inhibitor Testsmentioning
confidence: 99%
“…The rapid receptor tests considered in this study were designed for the specific detection of beta-lactam and tetracycline residues in milk presenting detection capabilities equal to or below the MRLs for most beta-lactams and tetracyclines employed by veterinarians (Beltrán et al, 2013(Beltrán et al, , 2014a and, consequently, higher detection rates for these antibiotics in milk are obtained.…”
Section: Discussionmentioning
confidence: 99%